On The Unified Scheme Of y- Ray Emitting Jetted Active Galactic Nuclei - Audu, A. I.; Odo, F. C.; Iyida, E. U.; Okike, O.; Ubachukwu, A. A. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
The discovery of y - ray emitting Seyfert galaxies has opened a new unified scheme of active galactic nuclei (AGN) in which jetted Seyfert galaxies are viewed as young counterparts of radio loud AGN. Открытие сейфертовских галактик с гамма-излучением позволило представить новую унифицированную схему активных ядер галактик (АЯГ), в которой сейфертовские галактики со струями (джеты) рассматриваются как молодые аналоги радиогромких АЯГ.
Keywords: Astrophysics